Sexual and reproductive health (SRH) needs for forcibly displaced adolescent girls and young women (10-24 years old) in humanitarian settings: a mixed-methods systematic review - Rachel E. Soeiro; José Paulo de Siqueira Guida; Juliana da-; Maria Laura Costa (BMC, 2023)
Abstract Background Globally, there are 42 million women and girls estimated to be forcibly displaced. Adolescent girls and young women in humanitarian settings have their sexual and reproductive health (SRH) neglected. This systematic review aimed to describe SRH obstacles that adolescent girls and young women (10-24 years old) face in humanitarian settings in line with the Sustainable Development Goals. Methods We conducted a mixed-methods systematic review in six databases, focusing on migrant women ages 10 - 24and their SRH outcomes. The mixed-methods appraisal tool was used to evaluate the quality of the studies. This review follows PRISMA and the Systematic Review Guidelines from the Centre for Reviews and Dissemination recommendations. Results Among the 1290 studies screened by abstracts, 32 met the eligibility criteria: 15 were qualitative, 10 were quantitative and seven were mixed-methods studies. Most studies were performed in the last four years, in African countries. They discussed the increased frequency of adolescent pregnancies (16-23%), lack of contraceptive use and access (8-32%), poor menstrual hygiene management (lack of water, shortage of menstrual hygiene supplies), ignorance and stigma about sexually transmitted infections and HIV, a higher number of child, early and forced marriage or partnership and sexual and gender-based violence, challenging to obtain SRH information/knowledge/access, and unmet SRH needs. Conclusion Migration is a current issue. Although there is a growing number of studies on adolescent girls and young women's SRH in humanitarian settings, this population remains overlooked, and face several challenges in SRH. There is a need for targeting interventions on SRH.